Refractory granulomatous lobular mastitis associated with subpectoral abscess and localized Salmonella infection: A case report - Keiko Kubota; Takashi Kurabayashi; Masanori Tasaki; Hirotaka Asato; Takuya Iida (JPRAS Open)
We report a rare granulomatous lobular mastitis (GLM) associated with Salmonella spp. infection in a 41-year-old woman presenting as a subpectoral abscess. Diagnosis was delayed due to negative routine cultures and atypical presentation. Surgical excision combined with long-term levofloxacin therapy achieved full recovery. Effective treatment requires antimicrobial coverage and elimination of static secretions in the mammary gland to prevent recurrence. Our case presents a unique perspective by illustrating how Salmonella, a facultative intracellular pathogen that targets macrophages and other immune cells, may secondarily infect a GLM lesion, characterized by dense infiltration of immune cells.